β-adrenergic receptor-induced E-S potentiation in the dorsal and ventral hippocampus - Trompoukis, George; Miliou, Athina; Papatheodoropoulos, Costas (Frontiers in Synaptic Neuroscience, 2024)
β-adrenergic receptors (β-ARs) play a critical role in modulating learning, memory, emotionality, and long-term synaptic plasticity. Recent studies indicate that β-ARs are necessary for long-term potentiation (LTP) induction in the ventral hippocampus under moderate synaptic activation conditions that do not typically induce LTP. To explore potential dorsoventral differences in β-AR-mediated effects, we applied the β-AR agonist isoproterenol (10 μM, 30 min) to dorsal and ventral hippocampal slices, recording field excitatory postsynaptic potentials (fEPSPs) and population spikes (PSs) from the CA1 region. Isoproterenol induced robust, long-lasting PS increases, with effects three times greater in the dorsal compared to the ventral hippocampus. Isoproterenol did not significantly affect fEPSP in either segment of the hippocampus, leading to strong excitatory-to-spike (E-S) potentiation—twice as large as that in the ventral hippocampus. E-S potentiation was not associated with significant paired-pulse inhibition changes in either hippocampal segment. These differences do not appear to result from β1-AR expression levels, as they are comparable across dorsal and ventral hippocampal regions. Overall, the findings suggest that β-AR activation enhances the dorsal hippocampus’s role during stress, facilitating heightened alertness, rapid spatial information processing, and effective navigation necessary for “fight-or-flight” responses.